2015
DOI: 10.1002/jclp.22155
|View full text |Cite
|
Sign up to set email alerts
|

Active and Passive Problem Solving: Moderating Role in the Relation Between Depressive Symptoms and Future Suicidal Ideation Varies by Suicide Attempt History

Abstract: Objective Research suggests that being unable to generate solutions to problems in times of distress may contribute to suicidal thoughts and behavior, and that depression is associated with problem solving deficits. This study examined active and passive problem solving as moderators of the association between depressive symptoms and future suicidal ideation (SI) among suicide attempters and non-attempters. Method Young adults (n = 324, 73% female, Mage = 19, SD = 2.22) with (n = 78) and without (n = 246) a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“… 114 In accord with the latter explanation, research suggests that poorer problem-solving abilities are highly associated with suicide attempts 115 and that those who attempt suicide tend to perceive themselves as passive problem solvers. 116 Clearly, more research needs to be conducted in examining which of these explanations are more viable. These findings could be beneficial to clinicians charged with providing treatment aimed at ameliorating the effects of childhood maltreatment for younger children.…”
Section: Discussionmentioning
confidence: 99%
“… 114 In accord with the latter explanation, research suggests that poorer problem-solving abilities are highly associated with suicide attempts 115 and that those who attempt suicide tend to perceive themselves as passive problem solvers. 116 Clearly, more research needs to be conducted in examining which of these explanations are more viable. These findings could be beneficial to clinicians charged with providing treatment aimed at ameliorating the effects of childhood maltreatment for younger children.…”
Section: Discussionmentioning
confidence: 99%
“…The style of problem solving also seems to be related to suicidal behavior. Quinones et al ( 39 ) found that patients who attempt suicide tend to present more passive strategies of solution of problems, that is, they are dependent on the action of other people, related to luck and chance or over time.…”
Section: Cognition and Suicide Behaviormentioning
confidence: 99%
“…At least part of the effectiveness of mindfulness-based interventions for suicide prevention has also been related by means of improvement in problem solving, as well as attentional dyscontrol and abnormal stress response ( 43 ). Thus, therapies with the aim of improve problem-solving abilities, especially active problem solving ( 39 ), should be considered in individuals at higher risk for suicide.…”
Section: Cognition and Suicide Behaviormentioning
confidence: 99%
“…The attrition rate was 10% (16 out of 160 participants did not complete the follow‐up), and one additional participant was excluded due to missing data at follow‐up. Note that the larger sample from which the present one was selected has been described elsewhere (Quiñones, Jurska, Fener, & Miranda, ), and the present sample only includes individuals who completed measures of emotion reactivity and comfort expressing emotions (described below) and who took part in the study's 12‐month follow up.…”
Section: Methodsmentioning
confidence: 99%